Pelatihan Membuat Karakter Animasi Menggunakan Aplikasi Scratch - Deden Rosid Waltam; Wawan Budiarto (Lembaga Pengembangan Kinerja Dosen, 2025)
Training in creating animated characters using the Scratch application serves as an introduction to block-based programming fundamentals that are simple, easy to operate, interactive, and engaging. This training offers promising competency outcomes, as students can further develop their skills through animated stories, games, or presentations. Since 2018, the Ministry of Education and Culture has promoted the integration of informatics education into the 2013 curriculum, including computational thinking skills, which are essential for both current and future generations. The partner for this community service training activity is the students of MTs Pembangunan Nurul Islam, located in Sarimulya, Setu, South Tangerang. This initiative is a tangible step toward implementing informatics learning through the introduction of block-based programming fundamentals. The training involved stages of introduction, instruction, and guidance in using the application. Based on observations and discussions with the partner school, several issues were identified in learning Information and Communication Technology (ICT). One of the causes is students’ lack of awareness of the importance of learning programming fundamentals, coupled with the stigma that programming is difficult, uninteresting, and boring. To address both technical and management issues, the proposed solutions in this community service program include: first, facilitating and providing guidance on the use of the Scratch application for MTs students, with the hope that they will understand basic programming without fear or difficulty. Second, offering engaging, interactive, simple, and easy-to-understand lessons on basic programming using Scratch, by providing example projects such as creating animated characters. The training program was implemented smoothly, and all participating students enthusiastically followed each stage of the training. Their motivation was encouraged to become familiar with programming, increasing their interest, understanding, and confidence in basic programming skills. The ultimate goal is to foster students' interest, knowledge, and skills while boosting their self-confidence in ICT learning, particularly in basic programming.